3.3 µm interband-cascade resonant-cavity light-emitting diode with narrow spectral emission linewidth. (2nd November 2020) - Díaz-Thomas, D A; Stepanenko, O; Bahriz, M; Calvez, S; Batte, T; Paranthoen, C; Patriarche, G; Tournié, E; Baranov, A N; Almuneau, G; Levallois, C; Cerutti, L
Abstract: We demonstrate an interband cascade resonant cavity light emitting diode (IC-RCLED) operating near 3.3 µ m at room temperature. The device is composed of a Sb-based type-II interband-cascade active zone enclosed between two distributed Bragg mirrors (DBR). The bottom high reflective DBR is composed of GaSb/AlAsSb quarter-wave layers. A metamorphic III-As region is grown after the active zone to benefit from the AlOx technology for efficient electro-optical confinement. The structure is finished with a top ZnS/Ge dielectric DBR. The devices with oxide aperture ranging from 5 µ m to 35 µ m were studied in the continuous wave regime. The fabricated IC-RCLEDs operated up to 80 °C (set-up limited) and exhibited narrow emission spectra with a full width half maximum of 21 nm, which is 20 times smaller compared with conventional IC-LEDs. The narrow emission line and its weak temperature dependence make the fabricated devices very attractive for low cost gas sensors.